A Modified Simulation of Cyert, Feigenbaum, and March's Duopoly Model - Tuckman, Howard P.; Holmblad, L. Peter (Management Science, 1972)
This paper utilizes a duopoly model to simulate the effects of various management rules of thumb and of changing economic conditions on the market share and profit-goals of the firm. Part I presents and discusses a behavioral model, Part II gives the initial market conditions and the parameters for the alternative simulations, and the remaining sections discuss the effects of the parameter changes. Several findings are of interest to management scientists. If a firm incorrectly estimates market demand its market and profit share will decrease. Estimates of the market demand curve slope which are far away from the true slope have a lesser proportional effect on the firm's share of the market than estimates close to the “true” slope. If costs rise rapidly due to internal slack, the price of a product will rise, market output will fall, and the two firms will have lower profit goals. Moreover, policies which encourage both short- and long-run expansion result in a larger share of the market for the newer firm. The paper ends with recommendations for further development of the model.